Membedah Komodifikasi Isi Pesan Mini Drama Line “Nic And Mar” (Analisis Semiotika John Fiske Terhadap Mini Drama Line) - Indra Hutami; Freddy Yusanto; Catur Nugroho (Universitas Trunojoyo Madura, 2018)
Mobile mini drama of the Line is a mini-series that narrate the characters who play a part in a story which has drama genre. One of them is a mobile mini drama Line